High frame rate blood speckle tracking echocardiography: left ventricle vortex analyisis in healthy children and in congenital heart disease. (4th February 2022) - Cantinotti, M; Marchese, P; Assanta, N; Van Den Eynde, J; Franchi, E; Shelby, K
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: High-frame rate blood speckle tracking (BST) echocardiography is a new method, for the evaluation of intracardiac flow, independent of the insonation angle. Left ventricle, throughout cardiac cycle, creates a vortical flow still poorly analysed in children with congenital heart disease (CHD). Aim of this study is to evaluate the characteristics of left ventricular (LV) vortices in healthy children and in those with CHD. Methods: Characteristics of LV vortices were acquired on standard 4-chamber view and BST images from 230 healthy children (median age 5.96 years, range 2.9-10.1 years) and 72 children with CHD (median age 1.33 years, IQR 0.2-7.12 years). Both groups were compared after propensity matching. Multiple linear regression was used to identify factors that independently influence vortex characteristics. Results: Feasibility of vortex imaging was 97% for healthy children and 96.7% for CHD. After propensity matching, there were mild significant differences in vortex distance to apex, distance to interventricular septum, height, width, sphericity index. Indexed by BSA Vortex Area (VAi) was significantly higher on CHD patients than healthy subjects (p < 0.0001).  However, multiple regression analysis exposed significant associations of LV morphology with vortex characteristics: a VAi >0.98 can predict an abnormal LV morphology (Sensibility 73%, Specificity 83%). Furthermore, CHD involving LV volume or pressure overload were both associated with vortices localized closer to the IVS. Conclusions: LV vortex analysis using high-frame rate BST echocardiography is feasible in healthy children and in those with CHD. Since vortices are associated with LV morphology and are altered in some CHDs, vortices might yield diagnostic and prognostic value. Future studies are necessary to further establish applications of vortex imaging in the clinical setting.